The Future of the European Single Market for Financial Services From a Polish Perspective - Kohtamäki, Natalia (Maastricht 30: A Central European Perspective, 2025)
The single financial market is still in statu nascendi, i.e. in the process of being established. Like a litmus test, it reacts to the crises regularly faced by the European Union. There are two main types of turbulence; those taking place within global financial markets (e.g. the 2008–2010 credit crunch), and those generating systemic risks from outside of the financial structures (e.g. the refugee migration crisis of2015, which was connected to Russia’s aggression against Ukraine of 2022, or the pandemic crisis of 2020). Both directly affect the financial sector which is deeply integrated in the EU Member States after 50 years of harmonisation efforts (first banking directive 1977). Although financial integration is generally regarded positively as the main driver of economic development in Member States, it should beborne in mind that the agenda for change is far from complete and that the single financial market will be increasingly challenged by technological revolutions in the sector, in particular the emergence of FinTechs. Member States can find they are a part of the structures of the European executive order (institutional and normative mechanisms) in the financial sector in different ways. This article attempts to provide a brief overview of the single financial market from the perspective of Poland, a Member State which, having joined the European Union in 2004, entered the already relatively well developed institutional structures of the EU financial sector, and had to learn to function effectively from within them. Keywords: financial market, integration of financial markets, financial safety net, European System of Financial Supervision, banking union